2013
DOI: 10.1111/tpj.12245
|View full text |Cite
|
Sign up to set email alerts
|

Cotton GhCKI disrupts normal male reproduction by delaying tapetum programmed cell death via inactivating starch synthase

Abstract: SUMMARYAnther infertility under high temperature (HT) conditions is a critical factor contributing to yield loss in cotton (Gossypium hirsutum). Using large-scale expression profile sequencing, we studied the effect of HT on cotton anther development. Our analysis revealed that altered carbohydrate metabolism or disrupted tapetal programmed cell death (PCD) underlie anther sterility. Expression of the Gossypium hirsutum casein kinase I (GhCKI) gene, which encodes a homolog of casein kinase I (CKI), was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 46 publications
6
120
0
Order By: Relevance
“…the reduction of Glc content in anthers (Min et al, 2013). These results indicated that sugar homeostasis, especially the decrease in Glc content in anthers, correlated for anther abortion in H05 under HT.…”
Section: Ht Disrupted Cotton Anther Carbohydrate Metabolism Pathwaysmentioning
confidence: 61%
See 4 more Smart Citations
“…the reduction of Glc content in anthers (Min et al, 2013). These results indicated that sugar homeostasis, especially the decrease in Glc content in anthers, correlated for anther abortion in H05 under HT.…”
Section: Ht Disrupted Cotton Anther Carbohydrate Metabolism Pathwaysmentioning
confidence: 61%
“…However, the mechanism of bud shedding under HT is unknown. Based on our previous research, the expression of GhCKI was induced earlier in anthers by HT, which regulated anther abortion and caused bud shedding (Min et al, 2013). To globally identify the genes and pathways participating in cotton anther development under HT, we chose two cotton lines (the HT-tolerant 84021 and the HT-sensitive H05), two temperature regimes (NT, 28°C-35°C/20°C-28°C day/night; HT, 35°C-39°C/29°C-31°C day/night), and three anther development stages (TS, TDS, and ADS), corresponding to crucial stages at which male reproductive organs are sensitive to stresses (Sato et al, 2002;Endo et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations